Unfriendly customer behaviors and employees’ psychological capital: The role of health symptoms and positive humor events - Junça-Silva, A.; Lopes, R. R. (Current Psychology, 2023)
This study examined the indirect effect and moderators that may explain the link between unfriendly customer behaviors and workers’ psychological capital with a sample of 380 employees. We hypothesized that perceived health symptoms would have an indirect effect on the link between unfriendly customer behaviors and psychological capital. We also hypothesized a moderated mediation model, in which positive humor events would moderate the indirect effect. Results show that the negative association between unfriendly customer behaviors with psychological capital was due to an increased level of perceived health symptoms. Moreover, positive humor events moderated the link between unfriendly customer behaviors and perceived health symptoms, such that the link was stronger when the frequency of positive humor events was low to moderate. This study addresses a major gap in the positive psychology literature by attempting to examine why unfriendly customer behaviors relate to decreased psychological capital and what factors influence in this relation. Practical implications are further discussed.